Odpowiedzi

2009-12-02T20:12:25+01:00
A)
y+2-(3-x)=0
x-2=5-(2-y)

y+2-3+x=0
x-2=5-2+y

x+y=1
x-y=5
--------
2x=6 /:2
x=3

x+y=1
3+y=1
y=1-3
y=-2

x=3
y=-2

b)
3(x-y)+4x=8
3(x-5y)=5-9y

3x-3y+4x=8
3x-15y=5-9y

7x-3y=8
3x-15y+9y=5

7x-3y=8 /*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5
---------------
-11x=-11 /:(-11)
x=1

3x-6y=5
3-6y=5
-6y=5-3
-6y=2 /:(-6)
y=⅓

x=1
y=⅓

c)
3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=9+11
10x-15x+3y-5y=2+2

6x+4y=20
-5x-2y=4 /*2

6x+4y=20
-10x-4y=8
-----------------
-4x=28 /:(-4)
x=-7

6x+4y=20
6*(-7)+4y=20
-42+4y=20
4y=20+42
4y=62 /:4
y=15,5

x=-7
y=15,5
1 5 1